PRODUCTIVITY HYBRIDS SUGAR-BEETS DEPENDING OF NUTRITION NORMS IN THE PRIDNESTROVIE TERMS - Яцева, О. А.; Бучковський, Д. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Relevance of the topic is to contribute to the stabilization in sugar production in Ukraine by improving the productivity of sugar beet hybrids depends of nutrition norms. We investigated in research normal nutrition norm(the rate of planned productivity of 50 t/ha) and higher nutrition norm(the rate of planned productivity of 60 t/ha); contents of sugar in roots sugar-beets and collecting sugar. Researches were conducted during 2015-2016 years on the experimental field research and production center “Podillja”. Where laid threefactors field researches to study nutrition norms on the rate of planned productivity and plant density of sugar-beets hybrids. On the results of research; we have found that; the weight of root and yield grew on all hybrids on higher nutrition norm comparing with normal nutrition. But; better harvest indicators were on all nutrient norms are Avtoritetnyi; Vavilov and Ronald; than Yashin. With increase yield on higher nutrition norm; sugar indicators decrease a little bit. On control and hybrid Vavilov sugar indicators decrease on 0;3%; Ronald - 0;1% and most decrease was in hybrid Yashin - 0;9%; comparing with normal nutrition norm. Highest indicator of collecting sugar has been on higher nutrition norm at hybrids Vavilov; Ronald and Avtoritetnyi. Results of field and lab research gave the opportunity optimisation fertilization norm of mineral nutritions for studied hybrids; which in turn can provide higher productivity and technological quality indicators roots of sugar-beets.